Examination of the Population Density Impact on Major Air Pollutants: A Study in the Case of Germany - Fuladlu, Kamyar; Altan, Haşim (Springer Nature, 2022)
Background: Today, there is a profound shift in the study of atmospheric pollutants at an urban scale especially due to their negative effects on humans and the environment. Atmospheric pollutants are emitted as a result of rapid urbanization, burning fossil fuels, deforestation, and agricultural intensification. The majority of studies believe cities have both the highest pollution rates and the highest impact targets. Unfortunately, the alteration of atmospheric pollutant patterns was faster than planners were able to come up with solutions. Major Air Pollutants (MAPs) are considered one of the important groups of atmospheric pollutants. Nitrogen Dioxide (NO2) and Sulfur Dioxide (SO2) are the main MAPs, which are released from road transport and are mostly exhaust emissions arising from fuel combustion. Aim and Method: Until a few years ago, monitoring MAPs, including NO2 and SO2 pollutants, was not as easy as today. Recently, the Sentinel-5 Precursor (S5P) satellite was successfully launched and scenes were released. Therefore, monitoring MAPs with the use of Remote Sensing (RS) and Geographical Information System (GIS) became possible. Accordingly, the current study aims to monitor NO2 and SO2 pollutants in the case of Germany as a country scale. Besides, this study has examined the relationship between the population density; NO2 and SO2 pollutants with the use of RS and GIS on the same scale as the use of a regression model. Result: Obviously, the concentration of the NO2 and SO2 pollutants over the cities is a result of mutual complex factors like meteorological situation, geographical location, population density, and land-use land-cover. Therefore, it cannot be stated that the population density contributes to the increase of pollutants. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
2nd International Conference on Urban Regeneration and Sustainability, URS 2020 -- 2020-10-07 through 2020-10-08 -- Virtual, Online -- 282169
Keywords: Germany; Major air pollutants; Nitrogen dioxide; Remote sensing; Sentinel-5 precursor satellite; Sulfur dioxide